2017
DOI: 10.1002/prp2.303
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet irradiation increases green fluorescence of dihydrorhodamine (DHR) 123: false-positive results for reactive oxygen species generation

Abstract: Dihydrorhodamine (DHR) 123 is a fluorophore commonly used for measuring reactive oxygen species (ROS), often after exposing cells to ultraviolet (UV) irradiation or oxidative burst inducers such as Phorbol 12‐myristate 13‐acetate (PMA). However, the negative effects of UV irradiation on oxidation of DHR123 itself to green fluorescence rhodamine (R) 123 under different experimental conditions (e.g., different buffers, media, cells, ROS detection techniques) have not been fully appreciated. We determined the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…To determine the source of ROS production during UV-induced NETosis, we studied both types of ROS. hypochlorous acid (HOCl) produced during NOX-dependent NETosis is known to oxidise non-fluorescent DHR123 molecules to green fluorescent R123 molecules 34 . DHR123 plate reader assays showed that PMA, but not UV exposure, induced NOX-dependent ROS production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the source of ROS production during UV-induced NETosis, we studied both types of ROS. hypochlorous acid (HOCl) produced during NOX-dependent NETosis is known to oxidise non-fluorescent DHR123 molecules to green fluorescent R123 molecules 34 . DHR123 plate reader assays showed that PMA, but not UV exposure, induced NOX-dependent ROS production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The e − generated by Nox reacts with molecular O 2 to generate superoxide among other ROS, which are important for NETosis ( 15 , 16 ). Therefore, we measured intracellular ROS by DHR123 as previously described ( 5 , 7 , 14 ). Neutrophils were preloaded with DHR123 and activated with or without PMA at six different pH levels.…”
Section: Resultsmentioning
confidence: 99%
“…DHR123 dye (Scientific Inc., MA, USA) was used to measure the intracellular ROS production. The neutrophils were preloaded with DHR123 (20 μM) for 10 min as per manufacturer’s instructions with brief modification as we reported earlier ( 5 , 7 , 14 ). After washing the extracellular DHR123 dye, cells were resuspended in fresh RPMI (10 mM HEPES) media and 50 μL of 50,000 cells, seeded into 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of salt on ROS production by neutrophils was assessed by DHR123 dye (Life Technologies). ROS oxidize DHR123 into R123, which emits a green fluorescence signal ( 36 ); thus, the amount of the green fluorescence signal indicates the amount of ROS production. Cells were preincubated with 25 µM of DHR123 dye for 15 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%